Study on Detection of Carbapenemases In Clinical Isolates Of Family Enterobacteriaceae (International Journal of Scientific Research and Management (IJSRM), 2015)
Enterobacteriaceae group of organisms are inhabitants of the intestinal tract.They are the source of community and hospital acquired infection.the carbapenems are recommended as last choice in treating in serious infections caused by multi drug resistance Gram negative bacilli and the emergence of Carbapenem resistant Enterobacteria is therefore worrisome as the antimicrobial armamentarium consequently is restricted.Objective: The study is under taken with a view to generally screen the Gram negative rods for the production of Carbapenemase as these enzymes do not always produce resistant breakpoints for Carbapenems using standardized susceptibility testing methods.Materials and Methods:A total of 200 samples were processed. The samples inoculated onto Nutrient agar, Blood agar, Macconkey agar and the colonies tested for motility, catalase and oxidae test. sugar fermentation methods and biochemical tests were performed. Antibiotic sensitivity was done by Kirby bauer disc diffusion method.Carbapenemase detection was done by Modified Hodge method.Results:Among 200 samples processed, the highest no.of samples were taken from the age group 41-50yrs(45). Highest isolated Enterobacteriaceae was Escherichia coli(102) followed by klebsiella (88).130 samples showed resistance to Carbapenem antibiotics.Among them,50 Enterobacteriaceae showed Modified Hodge test positive.In which, Eschericia coli was the highest(42)of 84%followed by Klebsiella sps(6)of 12%.Conclusion: our study findings are contrary to the belief. Therefore it is recommended that large sample based studies may be taken up in which may throw better light.a